Pelatihan dan Pendampingan Penulisan Artikel Ilmiah bagi Guru Sekolah Muhammadiyah di Kabupaten Malang - Arif Setiawan; Gigit Mujianto; Akhsanul In’am (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING AND ASSISTANCE IN WRITING SCIENTIFIC ARTICLES FOR MUHAMMADIYAH SCHOOL TEACHERS IN MALANG REGENCY. Writing scientific papers is an obligation that must be done by a teacher in carrying out duties as a teacher. This service activity aims to train and assist Muhammadiyah School teachers in Malang Regency to carry out scientific article writing activities. The target audience for this community service activity is the teachers of SD Muhammadiyah 8 Dau Malang and SMP Muhammadiyah 6 Dau Malang. The number of target audiences in this training and mentoring activity was 20 teachers consisting of 10 teachers from SD Muhammadiyah 8 Dau Malang and 10 teachers from SMP Muhammadiyah 6 Dau Malang. The location of the two schools is located in the same place in Dau Mulyoagung Jetis Malang Regency. Based on the evaluation of training and mentoring activities, 17 teachers complete the activity bills in the form of scientific articles. Among 17 teachers, 10 teachers are from SD Muhammadiyah 8 Dau and 7 other teachers come from SMP Muhammadiyah 6 Dau. Training and mentoring activities have helped teachers of SD Muhammadiyah 8 Dau and SMP Muhammadiyah 6 Dau to write scientific articles in the form of thoughts/studies and research results.